High-light-transmittance ultrathin PE heat shrinkage film and preparation method thereof
By adopting a three-layer structure with a high light transmittance ultra-thin PE heat shrink film, combined with type I and II MLLDPE, HDPE and other materials, the existing PE heat shrink film has been solved, and the film is thinned, improving the light transmittance and enhancing the mechanical properties.
Patent Information
- Application Number
- CN202411761422.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-04-25
AI Technical Summary
The existing PE heat shrink film has a large thickness and poor transparency, which affects the appearance of the cargo packaging. At the same time, the decrease in the film thickness leads to a poor mechanical properties.
A three-layer structure with a high light transmittance ultra-thin PE heat shrink film is used. The outer layer and the inner layer use type I MLLDPE as the main material, and the middle layer uses type II MLLDPE, and HDPE, opening agent, PPA additive and tackifying resin are added. It is prepared by coextrusion molding, blowing, cooling, traction, corona and winding processes.
The thickness reduction of the heat shrink film, the light transmittance improvement, the tensile resistance, puncture resistance and tear resistance of the heat shrink film are achieved, while the adhesion of the inner layer and the oil and stain-proof effect of the outer layer are enhanced.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of packaging films, and more specifically, to a high-transmittance ultra-thin PE heat shrinkable film and a preparation method thereof. Background Art
[0002] With the continuous development of my country's economy, the demand for heat shrink film in the packaging industry is increasing, and the scope of application is also expanding. It not only has good comprehensive performance in mechanical properties, packaging, storage, transportation, moisture resistance and appearance, but is also easy to recycle and recycle raw materials, meeting environmental protection requirements, but also improves packaging efficiency on automatic packaging lines and reduces comprehensive packaging costs. It is gradually replacing traditional packaging forms and becoming the first choice for bulk assembly packaging.
[0003] PE heat shrinkable film has excellent physical and mechanical properties such as tensile strength and breaking strength, and can achieve functions such as dustproof, waterproof, moisture-proof, and oil-proof. In addition, PE heat shrinkable film is light in weight, low in cost, recyclable, and has good protective effect. It is sought after by companies in the fast-moving consumer goods industry such as beer, mineral water, and beverages, and is widely used in the whole-piece cluster packaging and transportation of products such as cans, glass bottles, and plastic bottles.
[0004] At present, most PE heat shrink films on the market are made of low-density polyethylene alone or a blend of low-density polyethylene and high-density polyethylene. Although the PE heat shrink film has good shrinkage and mechanical properties, the film product is thick, usually above 100μm, and the transparency of the film is poor. The film is flowery or white, which affects the appearance of the goods packaging. In order to achieve product promotion and brand promotion through outer packaging, and to avoid the waste of resources and pollution caused by color film printing, companies in the food and beverage industry need PE heat shrink film to show the internal product image more clearly and increase product visibility. Therefore, most PE heat shrink film manufacturers will reduce the film thickness to increase its light transmittance, but the reduction in film thickness will lead to the deterioration of its mechanical properties. Summary of the invention
[0005] In order to increase the light transmittance of a PE heat shrinkable film and increase its mechanical properties such as tensile strength, the present application provides a high-light transmittance ultra-thin PE heat shrinkable film and a preparation method thereof.
[0006] In the first aspect, the present application provides a high-transmittance ultra-thin PE heat shrinkable film, which adopts the following technical solution: A high-transmittance ultra-thin PE heat shrinkable film, comprising an outer layer, a middle layer and an inner layer arranged in sequence; the outer layer comprises the following raw materials in parts by weight: 880-920 parts of type I MLLDPE, 80-120 parts of HDPE, 2-6 parts of an anti-blocking agent, and 3-7 parts of a PPA additive; The middle layer comprises the following raw materials in parts by weight: 180-220 parts of LDPE, 560-640 parts of type II MLLDPE and 180-220 parts of HDPE; The inner layer comprises the following raw materials in parts by weight: 880-920 parts of type I MLLDPE and 80-120 parts of HDPE; The density of the type I MLLDPE is 0.918-0.92 g / cm 3 , melt index is 1-1.5g / 10min; The density of the type II MLLDPE is 0.905-0.935 g / cm 3 , the melt index is 0.5-0.8g / 10min.
[0007] By adopting the above technical scheme, type I MLLDPE is used as the main material in the outer layer and the inner layer, and a small amount of HDPE is added. MLLDPE is also called metallocene. MLLDPE has outstanding tensile properties, impact strength and puncture resistance. These properties can make the product thin-walled and thinnable, and can reduce the thickness of the heat shrink film, while improving the tensile strength, puncture resistance and tear resistance of the heat shrink film. HDPE has excellent deformation resistance, can maintain the stability and integrity of the film, and increase the maximum tensile force and friction that the heat shrink film can withstand; adding an opening agent to the outer layer can increase the fluidity of the product, reduce the friction coefficient, improve the production efficiency of the finished product, reduce the friction between the film materials, and make the film materials easier to unfold and shrink. The PPA additive can reduce the apparent viscosity and extrusion temperature of the outer layer, making the film materials easier to flow and form during processing. It can also eliminate melt fracture and die accumulation, reduce cross-linked gel and oxidized gel during extrusion, improve product quality, and improve the surface gloss of the film materials. The middle layer uses Type II MLLDPE as the main material, mixed with LDPE and HDPE. LDPE has the advantages of high strength, good toughness, heat resistance, cold resistance, etc. It also has good resistance to environmental stress cracking, impact strength and tear strength. It can increase the tensile performance of the heat shrink film under the thinning effect of Type II MLLDPE.
[0008] Optionally, 80-100 parts by weight of tackifying resin is also added to the inner layer.
[0009] By adopting the above technical scheme, the tackifying resin can significantly increase the adhesion between the heat shrink film and the packaged object, making the packaging tighter and firmer, not easy to fall off or loosen, better fixing and protecting the packaged object, and preventing the packaging from being damaged or the contents from being scattered due to factors such as vibration and impact during transportation or storage. In addition, the heat shrink film can adhere closely to the surface of the package during the shrinking process, reducing the difficulty and time of packaging, improving the packaging efficiency, and forming a smooth and compact appearance. The addition of the tackifying resin helps to maintain this appearance effect, making the packaging more beautiful and generous.
[0010] Optionally, the tackifying resin is prepared by blending and granulating EVA resin, maleic anhydride grafted PE and liquidambar resin in a mass ratio of 1:0.3-0.5:0.5-1.
[0011] By adopting the above technical solution, maleic anhydride grafted PE is modified and grafted with polyethylene as the main material, and its molecular chain includes both polar groups and non-polar groups. The main chain - (CH2-CH2) n -The non-polar group has good compatibility with the polyethylene layer. After heating and melting, it can form a whole with polyethylene, thereby improving the uniformity of the dispersion of the tackifier resin in the inner layer. In addition, the polar molecules of maleic anhydride can form a strong interaction with the polylactic acid molecular chain to improve the adhesion and mechanical strength of the PE heat shrinkable film. At the same time, it also improves the compatibility of the PE molecular chain with the EVA resin. When the three are blended and granulated, the maleic anhydride grafted PE can form a stable and uniform mixture with the EVA resin. Therefore, the maleic anhydride grafted PE can improve the compatibility of the EVA resin and the sweet gum resin, and make the tackifier resin in the inner layer. Evenly distributed, a stable and uniform melt is obtained; EVA resin has good transparency and viscosity, can produce good compatibility with the raw materials in the inner layer, improve the viscosity of the inner layer, make it better fit the packaged items, while maintaining the transparency of the heat shrink film, so that consumers can see the items in the packaging film more clearly, and can also improve the wear resistance and tear resistance of the heat shrink film; Liquidambar resin is an amorphous transparent glass-like solid formed after the volatile oil is removed by distillation, which can effectively improve the adhesion of the inner layer, increase the bonding force with the packaging, and can also adjust the softness of the heat shrink film, enhance weather resistance and water resistance.
[0012] Optionally, modified silica is further added to the tackifying resin, the mass ratio of modified silica to EVA resin is 0.1-0.2:1, and the modified silica is prepared by vapor-depositing perfluorodecyltrichlorosilane on silica at a vacuum degree of 85-90 kPa and room temperature for 100-120 minutes.
[0013] By adopting the above technical scheme, perfluorodecyltrichlorosilane is evenly deposited on the surface of nano-silica, which can make the nano-silica have hydrophobic and oleophobic properties, so that it can be evenly dispersed in tackifying resins such as EVA resin and sweet gum resin, increase the roughness of the inner layer, and to a certain extent improve the physical friction between the heat shrinkable film and the packaged object, which helps to maintain the adhesion state and reduce the risk of slipping. Moreover, after the vapor deposition of perfluorodecyltrichlorosilane, the modified silica can be evenly dispersed in the inner layer film without affecting the continuity of the heat shrinkable film. At the same time, controlling the addition amount of modified silica can reduce the impact on light transmittance.
[0014] Optionally, 15-20 parts by weight of anti-adhesion particles are also added to the outer layer.
[0015] By adopting the above technical solution, the addition of anti-adhesion particles can improve the anti-adhesion effect of the heat shrinkable film when it is rolled up and unrolled, and prevent the unrolling speed from being affected during the processing.
[0016] Optionally, the anti-adhesion particles are prepared by the following method: Chitosan and maleic anhydride are mixed, sealed and heated to 120-130°C, kept warm for 2-3 hours, washed until the pH is neutral, then adjusted to 11, centrifuged and washed until the pH is 7.8, added with distilled water, diluted to a chitosan concentration of 1-1.5wt%, then ultrasonically treated for 20-30 minutes, freeze-dried, and a modified chitosan aerogel is prepared, wherein the mass ratio of chitosan to maleic anhydride is 1:0.25-0.3; The epoxy resin, diethylenetriamine and nano-titanium dioxide are uniformly mixed to obtain an impregnation solution, the modified chitin aerogel is impregnated in the impregnation solution for 30-40 minutes by vacuum assistance, and then cured at 100-120° C. for 2-3 hours to obtain a matrix, wherein the mass ratio of the epoxy resin, diethylenetriamine and nano-titanium dioxide is 1:0.08-0.1:0.1-0.2; The substrate is placed in an ethanol solution of heptadecafluorodecyltriethoxysilane with a concentration of 1-1.5 wt %, immersed for 20-30 minutes, and then filtered, dried, and crushed.
[0017] Generally, inorganic anti-adhesion agents are used, but their particle size in plastic film is too coarse and their light transmittance is poor, which can easily affect the gloss and transparency of plastic film. However, if the particle size is too small, the dispersion performance is poor and it is easy to agglomerate, which affects the mechanical properties of plastic film. It also causes the plastic film to be uneven and the anti-adhesion effect is not obvious. By adopting the above technical scheme, chitin is acylated with maleic anhydride, and the hydrogen bonds and van der Waals forces between chitin fibers are fully destroyed after ultrasound to obtain chitin fiber bundles. In addition, the electrostatic repulsion between maleic anhydride-modified chitin prevents chitin fibers from agglomerating, and the dispersion is more uniform and the stability is better. It can reduce the scattering of light and reduce the impact on transparency. After freeze-drying, a uniformly distributed three-dimensional porous structure is obtained, and then a mixed solution of epoxy resin, curing agent and nano-titanium dioxide is used for vacuum impregnation, and the epoxy resin is injected into the modified chitin aerogel. The modified chitin aerogel can be in the epoxy resin matrix It is evenly dispersed inside, and the polarity of chitosan is reduced after modification, which improves the compatibility with epoxy resin, thereby improving the toughness and strength of the modified chitosan aerogel. In addition, epoxy resin has high transparency. Filling it into the modified chitosan aerogel can further reduce the scattering of light by the porous structure and improve transparency. Titanium dioxide has high transparency and excellent ultraviolet absorption ability, which increases the anti-adhesion effect of the composite material without affecting the transparency. Finally, heptadecafluorodecyl triethoxysilane is used to increase the hydrophobicity of the composite material and increase the oil and anti-fouling effect of the outer layer of the heat shrinkable film, while maintaining a high light transmittance.
[0018] Optionally, the density of the HDPE is 0.949-0.961 g / cm 3 , melt index is 0.7-0.82g / 10min; The density of the LDPE is 0.923-0.925 g / cm 3 , the melt index is 0.25-0.3g / 10min.
[0019] By adopting the above technical scheme, LDPE and HDPE with the above density and melt index have excellent toughness and outstanding optical properties, which can provide an excellent balance between processing and film properties for different resins, including stretchability, impact resistance and puncture resistance, and have a significant toughness improvement effect.
[0020] Optionally, the thickness ratio of the outer layer, the middle layer and the inner layer is 1:2.5-3:1.
[0021] By adopting the above technical solution, the heat shrinkable film with the above thickness can maintain excellent light transmittance and has strong tensile and tear resistance.
[0022] In a second aspect, the present application provides a method for preparing an ultra-thin PE heat shrinkable film with high light transmittance, using the following technical solution: A method for preparing a high-transmittance ultra-thin PE heat shrinkable film comprises the following steps: mixing raw materials of an outer layer, an inner layer and a middle layer according to a ratio, hot-melt granulating them respectively to obtain an inner layer material, an outer layer material and a middle layer material, and then co-extruding the three layers, cooling after inflation, pulling, coronaizing and rolling to obtain a PE heat shrinkable film.
[0023] By adopting the above technical solution, various raw materials of the inner layer, outer layer and middle layer are first mixed and granulated, so that the raw materials of each layer can be fully mixed, and the uniformity and stability of the raw materials of the inner layer, outer layer and middle layer can be improved.
[0024] Optionally, the extrusion temperature is 190-200° C., the blow-up ratio is 3.4-3.6, the corona power is 6.5-7.5 kW, and the pulling speed is 45-50 m / min.
[0025] In summary, this application has the following beneficial effects: 1. Since the density of the outer layer and the inner layer of this application is 0.918-0.92g / cm 3 , the melt index is 1-1.5g / 10min, and the density is 0.905-0.935g / cm in the middle layer. 3 , Type II MLLLDPE with a melt index of 0.5-0.8g / 10min, reduces the thickness of the heat shrinkable film, increases the light transmittance, and maintains the tensile, puncture and tear resistance of the plastic film.
[0026] 2. In the present application, it is preferred to add a tackifying resin made of EVA resin, maleic anhydride grafted PE, liquidambar resin and hydrophobically modified silica to the inner layer to increase the adhesion of the inner layer, improve the adhesion of the heat shrinkable film to the packaging, increase the packaging stability, and enhance the toughness and tear resistance of the plastic film while maintaining a high transparency of the plastic film.
[0027] 3. In the present application, anti-adhesion particles are added to the outer layer. The anti-adhesion particles are made of aerogel prepared from maleic anhydride-modified chitin. After vacuum impregnation with epoxy resin containing nano-titanium dioxide, hydrophobic treatment is performed using heptadecafluorodecyltriethoxysilane. Anti-adhesion particles with high transparency and good heat resistance can be obtained, which can increase the roughness of the outer layer, transform the contact between the films from the original surface-to-surface contact to point-to-point contact, reduce the adhesion of the outer layer when it is unrolled, and at the same time make the outer layer have a good hydrophobic and oil-proof effect. DETAILED DESCRIPTION
[0028] The following examples further illustrate the present application in detail.
[0029] Preparation Examples 1-6 of Anti-adhesion Particles
[0030] Preparation Example 1: (1) 100 g of chitosan and maleic anhydride were mixed, sealed and heated to 120°C, kept warm for 3 h, washed with anhydrous ethanol to remove the color, washed with pure water until the pH was neutral, adjusted to pH 11 with 1 mol / l sodium hydroxide aqueous solution, centrifuged and washed until the pH was 7.8, added with distilled water, diluted to a chitosan concentration of 1.5 wt%, then treated with 22 kHz ultrasound for 30 min, frozen for 2 h, and freeze-dried at -70°C and 10 Pa for 48 h to obtain a modified chitosan aerogel, wherein the mass ratio of chitosan to maleic anhydride was 1:0.3; (2) Epoxy resin E51, diethylenetriamine and nano-titanium dioxide were mixed evenly to obtain an impregnation solution, and the modified chitin aerogel was impregnated in the impregnation solution for 40 minutes using vacuum assistance, and then cured at 100°C for 3 hours to obtain a matrix. The mass ratio of epoxy resin E51, diethylenetriamine and nano-titanium dioxide was 1: 0.1:0.2; (3) The substrate was placed in an ethanol solution of heptadecafluorodecyltriethoxysilane with a concentration of 1.5 wt %, immersed for 30 min, and then filtered, dried, and crushed to 5 μm.
[0031] Preparation Example 2: (1) 100 g of chitosan and maleic anhydride were mixed, sealed and heated to 130°C, kept warm for 2 h, washed with anhydrous ethanol to remove the color, washed with pure water until the pH was neutral, adjusted to pH 11 with 1 mol / l sodium hydroxide aqueous solution, centrifuged and washed until the pH was 7.8, added with distilled water, diluted to a chitosan concentration of 1 wt%, treated with 22 kHz ultrasound for 20 min, frozen for 2 h, and freeze-dried at -70°C and 10 Pa for 48 h to obtain a modified chitosan aerogel, wherein the mass ratio of chitosan to maleic anhydride was 1:0.25; (2) Epoxy resin E51, diethylenetriamine and nano-titanium dioxide were mixed evenly to obtain an impregnation solution, and the modified chitin aerogel was impregnated in the impregnation solution for 30 minutes using vacuum assistance, and then cured at 120°C for 2 hours to obtain a matrix. The mass ratio of epoxy resin E51, diethylenetriamine and nano-titanium dioxide was 1: 0.08:0.1; (3) The substrate was placed in an ethanol solution of heptadecafluorodecyltriethoxysilane with a concentration of 1 wt %, immersed for 20 min, and then filtered, dried, and crushed to 5 μm.
[0032] Preparation Example 3: (1) 100 g of chitosan and maleic anhydride were mixed, sealed and heated to 120°C, kept warm for 3 h, washed with anhydrous ethanol to remove the color, washed with pure water until the pH was neutral, adjusted to pH 11 with 1 mol / l sodium hydroxide aqueous solution, centrifuged and washed until the pH was 7.8, added with distilled water, diluted to a chitosan concentration of 1.5 wt%, then treated with 22 kHz ultrasound for 30 min, frozen for 2 h, and freeze-dried at -70°C and 10 Pa for 48 h to obtain a modified chitosan aerogel, wherein the mass ratio of chitosan to maleic anhydride was 1:0.3; (2) The modified chitin aerogel was placed in an ethanol solution of heptadecafluorodecyltriethoxysilane with a concentration of 1.5 wt %, immersed for 30 min, and then filtered, dried, and crushed to 5 μm.
[0033] Preparation Example 4: (1) Chitosan was mixed with distilled water to a concentration of 1.5 wt%, and then subjected to 22 kHz ultrasonic treatment for 30 min, frozen for 2 h, and freeze-dried at -70 °C and 10 Pa for 48 h to obtain a modified chitosan aerogel; (2) Epoxy resin E51, diethylenetriamine and nano-titanium dioxide were mixed evenly to obtain an impregnation solution, and the modified chitin aerogel was impregnated in the impregnation solution for 40 minutes using vacuum assistance, and then cured at 100°C for 3 hours to obtain a matrix. The mass ratio of epoxy resin E51, diethylenetriamine and nano-titanium dioxide was 1: 0.1:0.2; (3) The substrate was placed in an ethanol solution of heptadecafluorodecyltriethoxysilane with a concentration of 1.5 wt %, immersed for 30 min, and then filtered, dried, and crushed to 5 μm.
[0034] Preparation Example 5: (1) 100 g of chitosan and maleic anhydride were mixed, sealed and heated to 120°C, kept warm for 3 h, washed with anhydrous ethanol to remove the color, washed with pure water until the pH was neutral, adjusted to pH 11 with 1 mol / l sodium hydroxide aqueous solution, centrifuged and washed until the pH was 7.8, added with distilled water, diluted to a chitosan concentration of 1.5 wt%, then treated with 22 kHz ultrasound for 30 min, frozen for 2 h, and freeze-dried at -70°C and 10 Pa for 48 h to obtain a modified chitosan aerogel, wherein the mass ratio of chitosan to maleic anhydride was 1:0.3; (2) Epoxy resin E51, diethylenetriamine and nano-titanium dioxide were mixed evenly to obtain an impregnation solution. The modified chitin aerogel was impregnated in the impregnation solution for 40 min using vacuum assistance, and then cured at 100 °C for 3 h to obtain a matrix, which was crushed to 5 μm. The mass ratio of epoxy resin E51, diethylenetriamine and nano-titanium dioxide was 1: 0.1:0.2.
[0035] Preparation Example 6: The difference from Preparation Example 1 is that no nano titanium dioxide is added. Example
[0036] Example 1: A high-transmittance ultra-thin PE heat shrinkable film, comprising an outer layer, a middle layer and an inner layer with a thickness ratio of 1:3:1. The raw material amounts of the outer layer, the middle layer and the inner layer are shown in Table 1. The density of type I MLLDPE in the outer layer and the inner layer in Table 1 is 0.92 g / cm 3 The melt index (190°C, 2.16kg) is 1g / 10min, selected from ExxonMobil, model 1018MA, and the density of HDPE in the outer layer, inner layer and middle layer is 0.961g / cm 3 The melt index (190°C, 2.16kg) is 0.7g / 10min, selected from ExxonMobil, model HTA-108, and the density of LDPE in the middle layer is 0.923g / cm 3 The melt index (190℃, 2.16kg) is 0.3g / 10min, selected from Maoming Petrochemical, model 2420D, and the density of type II MLLDPE in the middle layer is 0.935g / cm 3 The melt index (190℃, 2.16kg) is 0.5g / 10min, selected from ExxonMobil, model 3505MC, the opening agent in the outer layer is selected from Gaozhuo New Materials, model PEK-77, melt index is 1.6g / 10min, density is 0.94g / cm 3 , PPA additive is selected from Guangzhou Haocheng New Materials, model is HC-156.
[0037] The method for preparing the above-mentioned high-transmittance ultra-thin PE heat shrinkable film comprises the following steps: The raw materials of the outer layer, inner layer and middle layer are mixed according to the amounts in Table 1, and hot-melt granulated separately to obtain the inner layer material, the outer layer material and the middle layer material, and then three-layer co-extruded, and after inflation, cooled, pulled, corona and rolled to obtain the PE heat shrinkable film. The hot-melt granulation temperature of the outer layer material, the inner layer material and the middle layer material is 180°C, the temperature of the outer layer host is 190°C, the temperature of the middle layer host is 190°C, the temperature of the inner layer host is 190°C, the inflation ratio is 3.6, the corona power is 7.5KW, and the pulling speed is 45m / min.
[0038] Table 1 Raw material dosage of high light transmittance ultra-thin PE heat shrink film
[0039] Example 2: A high-transmittance ultra-thin PE heat shrinkable film, comprising an outer layer, a middle layer and an inner layer with a thickness ratio of 1:2.5:1. The raw material amounts of the outer layer, the middle layer and the inner layer are shown in Table 1. The density of type I MLLDPE in the outer layer and the inner layer in Table 1 is 0.918 g / cm 3The melt index (190°C, 2.16kg) is 1.5g / 10min, selected from ExxonMobil, model 1518CA, and the density of HDPE in the outer layer, inner layer and middle layer is 0.949g / cm 3 The melt index (190°C, 2.16kg) is 0.82g / 10min, selected from Japan Priman, model 7000F, and the density of LDPE in the middle layer is 0.925g / cm 3 The melt index (190℃, 2.16kg) is 0.25g / 10min, selected from Maoming Petrochemical, model 1810D, and the density of type II MLLDPE in the middle layer is 0.905g / cm 3 The melt index (190℃, 2.16kg) is 0.8g / 10min, selected from ExxonMobil, model 3505MC, the opening agent in the outer layer is selected from Gaozhuo New Materials, model PEK-77, melt index is 1.6g / 10min, density is 0.94g / cm 3 , PPA additive is selected from Guangzhou Haocheng New Materials, model is HC-156.
[0040] The method for preparing the above-mentioned high-transmittance ultra-thin PE heat shrinkable film comprises the following steps: The raw materials of the outer layer, inner layer and middle layer are mixed according to the amounts in Table 1, and hot-melt granulated separately to obtain the inner layer material, outer layer material and middle layer material, and then three-layer co-extruded, and after inflation, cooled, pulled, corona and rolled to obtain the PE heat shrinkable film. The hot-melt granulation temperature of the outer layer material, inner layer material and middle layer material is 180°C, the temperature of the outer layer host is 200°C, the temperature of the middle layer host is 200°C, the temperature of the inner layer host is 200°C, the inflation ratio is 3.4, the corona power is 6.5KW, and the pulling rate is 50m / min.
[0041] Example 3: A high-transmittance ultra-thin PE heat shrinkable film, which is different from Example 1 in that the amounts of raw materials used are as shown in Table 1.
[0042] Example 4: A high-transmittance ultra-thin PE heat shrinkable film, which is different from Example 1 in that 100 kg of tackifying resin is further added to the inner layer, and the tackifying resin is polyisobutylene.
[0043] Example 5: A high light transmittance ultra-thin PE heat shrinkable film, which is different from Example 1 in that 100 kg of tackifying resin is further added to the inner layer, and the tackifying resin is prepared by mixing and granulating EVA resin, maleic anhydride grafted PE, sweet gum resin and modified silica in a mass ratio of 1:0.5:1:0.2 at 120°C, and the EVA resin is selected from Mitsui Chemicals of Japan, with a brand of 460, and the maleic anhydride grafted PE is selected from Ningbo Yier Sanke Plastics, with a brand of Zhongke Xianxing , model 2120, preparation method of liquidambar resin: mix liquidambar resin and ethanol in a mass ratio of 1:1, heat the resin to 50℃ and melt for 60min, then filter, clarify and precipitate it, and then steam distill it at 130℃, distill it for 30min and then distill it under reduced pressure for 10min. The modified silica is made by vapor depositing perfluorodecyltrichlorosilane on silica at a vacuum degree of 90kPa and room temperature for 100min, and the silica particle size is 10μm.
[0044] Example 6: A high light transmittance ultra-thin PE heat shrinkable film, which is different from Example 1 in that 80 kg of tackifying resin is added to the inner layer, and the tackifying resin is prepared by mixing and granulating EVA resin, maleic anhydride grafted PE, sweet gum resin and modified silica in a mass ratio of 1:0.3:0.5:0.1 at 120°C, and the EVA resin is selected from Mitsui Chemicals of Japan, with a brand of 460, and the maleic anhydride grafted PE is selected from Ningbo Yier Sanke Plastics, with a brand of Zhongkexian The model is 2120. The preparation method of liquidambar resin is as follows: liquidambar resin and ethanol are mixed in a mass ratio of 1:1, the resin is heated to 50°C and melted for 60 minutes, then filtered, clarified, precipitated and purified, and then steam distilled at 130°C. After distillation for 30 minutes, vacuum distillation is performed for 10 minutes. The modified silica is prepared by vapor-depositing perfluorodecyltrichlorosilane on silica at a vacuum degree of 85 kPa and room temperature for 120 minutes. The silica particle size is 10 μm.
[0045] Example 7: A high-transmittance ultra-thin PE heat shrinkable film, which differs from Example 6 in that the silicon dioxide is not modified by vapor deposition of perfluorodecyltrichlorosilane.
[0046] Example 8: A high light transmittance ultra-thin PE heat shrinkable film, which differs from Example 6 in that liquidambar resin is not added.
[0047] Example 9: A high-transmittance ultra-thin PE heat shrinkable film, which differs from Example 6 in that maleic anhydride-grafted PE is not added.
[0048] Example 10: A high-transmittance ultra-thin PE heat shrinkable film, which differs from Example 6 in that 20 kg of anti-adhesion particles are further added to the outer layer, and the anti-adhesion particles are mica powder.
[0049] Example 11: A high-transmittance ultra-thin PE heat shrinkable film. The difference from Example 6 is that 20 kg of anti-adhesion particles are also added to the outer layer, and the anti-adhesion particles are made by Preparation Example 1.
[0050] Example 12: A high-transmittance ultra-thin PE heat shrinkable film. The difference from Example 6 is that 20 kg of anti-adhesion particles are also added to the outer layer, and the anti-adhesion particles are made by Preparation Example 2.
[0051] Example 13: A high-transmittance ultra-thin PE heat shrinkable film, which differs from Example 11 in that the anti-adhesion particles are made from Preparation Example 3.
[0052] Example 14: A high-transmittance ultra-thin PE heat shrinkable film, which differs from Example 11 in that the anti-adhesion particles are made from Preparation Example 4.
[0053] Example 15: A high-transmittance ultra-thin PE heat shrinkable film, which differs from Example 11 in that the anti-adhesion particles are made from Preparation Example 5.
[0054] Example 16: A high-transmittance ultra-thin PE heat shrinkable film, which differs from Example 11 in that the anti-adhesion particles are made from Preparation Example 6.
[0055] Comparative Example
[0056] Comparative Example 1: A high-transmittance ultra-thin PE heat shrinkable film, which is different from Example 1 in that type I MLLDPE is not added to the outer layer and the inner layer.
[0057] Comparative Example 2: A high light transmittance ultra-thin PE heat shrinkable film, which differs from Example 1 in that Type II MLLDPE is not added to the middle layer.
[0058] Performance testing
[0059] Heat shrinkable films were prepared according to the methods in the examples and comparative examples, and the properties of the heat shrinkable films were tested according to the following methods. The test results are recorded in Table 2.
[0060] 1. Thickness: Test in accordance with GB / T6672-2001 "Mechanical measurement method for thickness of plastic film and sheet".
[0061] 2. Light transmittance: The test shall be carried out in accordance with GB / T2410-2008 "Test method for light transmittance and haze of transparent plastics", with the detection wavelength of 600nm and the WGT-T light transmittance and haze tester.
[0062] 3. Tensile strength: Test in accordance with GB / T1040.3-2006 "Determination of tensile properties of plastics Part 3: Tests on films and sheets".
[0063] 4. Friction coefficient of the outer layer: Use MXD-01A friction coefficient tester to test the dynamic friction coefficient of the outer layer. The test environment temperature is 25-28℃, the humidity range is 40%RH-45%RH, the mass of the slider is 200g, the overall dimensions are 575mm(L)×310mm(W)×208mm(H), the test speed is 150mm / min, and the dynamic friction coefficient is calculated according to the following formula: μ=A / B, A: the average value when reaching the outer surface of the film for uniform sliding (g), B: the mass of the slider (g).
[0064] 5. Outer layer contact angle: Use a contact angle meter to test the outer layer wettability. The water drop volume is 5 μl, the temperature is 23 °C, and the relative humidity is 52%.
[0065] 6. Adhesion of the inner layer: Cut the test sample into appropriate size, prepare the stainless steel plate for testing, ensure that the surface of the steel plate is clean and flat, heat up until the heat shrink film is pressed against the surface of the stainless steel plate, ensure that there are no bubbles or impurities between the two, perform a tensile peel test, peel the film off the test stainless steel plate at 180°, test at a speed of 300 mm / min, perform 4 parallel tests, and calculate the average value.
[0066] Table 2 Performance test results of high transmittance ultra-thin PE heat shrink film
[0067] Combining the data in Table 2 with Examples 1-3, it can be seen that the PE heat shrinkable films prepared in Examples 1-3 have a relatively low thickness, high light transmittance, good transparency, high tensile strength, strong mechanical properties, the friction coefficient and contact angle of the outer layer need to be improved, and the adhesion of the inner layer is good.
[0068] Compared with Example 1, Example 4 further adds a certain amount of polyisobutylene as a tackifying resin to the inner layer. Table 2 shows that the adhesion of the inner layer of the PE heat shrinkable film prepared in Example 4 is significantly enhanced, but the transparency is reduced. This may be because polyisobutylene forms tiny particles or crystalline areas in the inner layer, resulting in light scattering, which affects the transmittance of the heat shrinkable film.
[0069] In Example 5 and Example 6, tackifying resins prepared from EVA, maleic anhydride grafted PE, liquidambar resin and modified silica are used. Table 2 shows that, compared with Example 1, the inner layer adhesion of the heat shrinkable films prepared in Example 5 and Example 6 is enhanced, and the light transmittance of the heat shrinkable films is increased.
[0070] Compared with Example 6, Example 7 does not add silicon dioxide and does not undergo vapor deposition using perfluorodecyltrichlorosilane. Table 2 shows that the transparency and tensile strength of the heat shrinkable film prepared in Example 7 are reduced, and the peel strength is weakened, indicating that the modified silicon dioxide can effectively reduce the impact on transparency while increasing the mechanical strength and inner layer adhesion.
[0071] Compared with Example 6, Example 8 and Example 9 do not add Liquidambar resin and maleic anhydride grafted PE, respectively. The data in Table 2 show that the inner layer adhesion of the heat shrinkable films prepared in Example 8 and Example 9 decreases.
[0072] Compared with Example 6, Example 10 adds anti-adhesion particles to the outer layer. Table 2 shows that the transparency of the heat shrinkable film prepared in Example 10 decreases, the contact angle of the outer layer decreases, but the dynamic friction coefficient of the outer layer increases, and the anti-adhesion effect of the outer layer increases.
[0073] In Example 11 and Example 12, the anti-adhesion particles prepared in Preparation Example 1 and Preparation Example 2 were used respectively. Compared with Example 6, the transparency of the heat shrinkable film was increased, the tensile strength was enhanced, the contact angle of the outer layer was increased, the oil and anti-fouling effect was improved, the dynamic friction coefficient was reduced, and the anti-adhesion effect was further improved.
[0074] In Example 13, the anti-adhesion particles prepared in Preparation Example 3 were used. Compared with Example 11, the transparency of the heat shrinkable film decreased, the tensile strength decreased, the contact angle between the outer layer and water decreased, and the anti-oil effect was weakened.
[0075] Compared with Example 11, the anti-adhesion particles in Example 14 are prepared by Preparation Example 4, and maleic anhydride is not used to modify the chitin. Table 2 shows that the transparency of the heat shrinkable film prepared in Example 14 is affected to a certain extent, and the tensile strength is weakened, and the hydrophobic angle is decreased.
[0076] Compared with Example 11, the anti-adhesion particles in Example 15 are made by Preparation Example 5, but are not immersed in the ethanol solution of heptadecafluorodecyltriethoxysilane. From the comparison of the data in Table 2, it can be seen that the contact angle of the heat shrinkable film prepared in Example 15 decreases, and the anti-oil effect is weakened.
[0077] Example 16 uses the anti-adhesion particles prepared in Preparation Example 6 without adding titanium dioxide. Compared with Example 11, the contact angle is reduced, the anti-oil effect is reduced, the dynamic friction coefficient is increased, the anti-adhesion effect is reduced, but the transparency is slightly improved.
[0078] Compared with Example 1, Comparative Example 1 does not add Type I MLLDPE to the outer layer and the inner layer. Compared with Example 1, Comparative Example 2 does not add Type II MLLDPE to the middle layer. The thickness of the heat shrinkable films prepared in Comparative Examples 1 and 2 increases, and the transparency decreases.
[0079] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high light transmittance ultra-thin PE heat shrinkable film, characterized in that: It comprises an outer layer, a middle layer and an inner layer arranged in sequence; the outer layer comprises the following raw materials in parts by weight: 880-920 parts of type I MLLDPE, 80-120 parts of HDPE, 2-6 parts of an opening agent, and 3-7 parts of a PPA additive; The middle layer comprises the following raw materials in parts by weight: 180-220 parts of LDPE, 560-640 parts of type II MLLDPE and 180-220 parts of HDPE; The inner layer comprises the following raw materials in parts by weight: 880-920 parts of type I MLLDPE and 80-120 parts of HDPE; The density of the type I MLLDPE is 0.918-0.92 g / cm 3 , melt index is 1-1.5g / 10min; The density of the type II MLLDPE is 0.905-0.935 g / cm 3 , the melt index is 0.5-0.8g / 10min.
2. The high light transmittance ultra-thin PE heat shrinkable film according to claim 1, characterized in that: 80-100 parts by weight of tackifying resin is also added to the inner layer.
3. The high light transmittance ultra-thin PE heat shrinkable film according to claim 2, characterized in that: The tackifying resin is prepared by blending and granulating EVA resin, maleic anhydride grafted PE and liquidambar resin in a mass ratio of 1:0.3-0.5:0.5-1.
4. The high light transmittance ultra-thin PE heat shrinkable film according to claim 3, characterized in that: Modified silica is also added to the tackifying resin, the mass ratio of the modified silica to the EVA resin is 0.1-0.2:1, and the modified silica is prepared by vapor-depositing perfluorodecyltrichlorosilane on silica for 100-120 minutes at a vacuum degree of 85-90 kPa and room temperature.
5. The high light transmittance ultra-thin PE heat shrinkable film according to claim 1, characterized in that: 15-20 parts by weight of anti-adhesion particles are also added to the outer layer.
6. The high light transmittance ultra-thin PE heat shrinkable film according to claim 5, characterized in that: The anti-adhesion particles are prepared by the following method: Chitosan and maleic anhydride are mixed, sealed and heated to 120-130°C, kept warm for 2-3 hours, washed until the pH is neutral, then adjusted to 11, centrifuged and washed until the pH is 7.8, added with distilled water, diluted to a chitosan concentration of 1-1.5wt%, then ultrasonically treated for 20-30 minutes, freeze-dried, and a modified chitosan aerogel is prepared, wherein the mass ratio of chitosan to maleic anhydride is 1:0.25-0.3; The epoxy resin, diethylenetriamine and nano-titanium dioxide are uniformly mixed to obtain an impregnation solution, the modified chitin aerogel is impregnated in the impregnation solution for 30-40 minutes by vacuum assistance, and then cured at 100-120° C. for 2-3 hours to obtain a matrix, wherein the mass ratio of the epoxy resin, diethylenetriamine and nano-titanium dioxide is 1:0.08-0.1:0.1-0.2; The substrate is placed in an ethanol solution of heptadecafluorodecyltriethoxysilane with a concentration of 1-1.5 wt %, immersed for 20-30 minutes, and then filtered, dried, and crushed.
7. The high light transmittance ultra-thin PE heat shrinkable film according to claim 1, characterized in that: The density of the HDPE is 0.949-0.961 g / cm 3 , melt index is 0.7-0.82g / 10min; The density of the LDPE is 0.923-0.925 g / cm 3 , the melt index is 0.25-0.3g / 10min.
8. The high light transmittance ultra-thin PE heat shrinkable film according to claim 1, characterized in that: The thickness ratio of the outer layer, the middle layer and the inner layer is 1:2.5-3:
1.
9. The method for preparing the high light transmittance ultra-thin PE heat shrinkable film according to any one of claims 1 to 8, characterized in that: The following steps are involved: The raw materials of the outer layer, inner layer and middle layer are mixed according to a proportion, hot-melt granulated separately to obtain the inner layer material, outer layer material and middle layer material, and then three-layer co-extruded, blown, cooled, pulled, corona-treated and rolled to obtain the PE heat shrinkable film.
10. The method for preparing the high light transmittance ultra-thin PE heat shrinkable film according to claim 9, characterized in that: The extrusion temperature is 190-200° C., the blowing ratio is 3.4-3.6, the corona power is 6.5-7.5 kW, and the pulling speed is 45-50 m / min.
Citation Information
Patent Citations
High-transmittance PE heat shrinkable film and preparation process thereof
CN111469519A
High-transmittance and high-gloss heat shrinkable film and preparation method thereof
CN112659690A
High-transparency polyethylene heat shrink film and preparation method thereof
CN116728930A